2007
DOI: 10.1002/term.24
|View full text |Cite
|
Sign up to set email alerts
|

State of the art and future directions of scaffold-based bone engineering from a biomaterials perspective

Abstract: Scaffold-based bone tissue engineering aims to repair/regenerate bone defects. Such a treatment concept involves seeding autologous osteogenic cells throughout a biodegradable scaffold to create a scaffold-cell hybrid that may be called a tissue-engineered construct (TEC). A variety of materials and scaffolding fabrication techniques for bone tissue engineering have been investigated over the past two decades. This review aims to discuss the advances in bone engineering from a scaffold material point of view. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
636
0
27

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 884 publications
(670 citation statements)
references
References 73 publications
7
636
0
27
Order By: Relevance
“…115,116 Research has shown that a synthetic bone scaffold should maintain its mechanical properties for at least 1-3 months after implantation (without shielding cells from mechanostimulation) and then should be totally resorbed through metabolic pathways after $12-18 months so that it does not impeded tissue ingrowth and regeneration. 59,117 Because of the difficulties associated with measuring the mechanical properties of bone and the synthetic scaffold during tissue regeneration and scaffold degradation in vivo, researchers have developed 3D computational modeling techniques with the goal of determining the optimal degradation rate of a synthetic scaffold. For example, assuming the scaffold degradation rate is proportional to the water penetration rate and ester bond hydrolysis (polymer degradation), and bone regeneration rate is governed by the rate equation for trabecular surface remodeling.…”
Section: Bone Biomimeticsmentioning
confidence: 99%
“…115,116 Research has shown that a synthetic bone scaffold should maintain its mechanical properties for at least 1-3 months after implantation (without shielding cells from mechanostimulation) and then should be totally resorbed through metabolic pathways after $12-18 months so that it does not impeded tissue ingrowth and regeneration. 59,117 Because of the difficulties associated with measuring the mechanical properties of bone and the synthetic scaffold during tissue regeneration and scaffold degradation in vivo, researchers have developed 3D computational modeling techniques with the goal of determining the optimal degradation rate of a synthetic scaffold. For example, assuming the scaffold degradation rate is proportional to the water penetration rate and ester bond hydrolysis (polymer degradation), and bone regeneration rate is governed by the rate equation for trabecular surface remodeling.…”
Section: Bone Biomimeticsmentioning
confidence: 99%
“…The need for synthetic bone grafts is clear, but their choice and design remain still complex due to many considerations such as material composition, architecture, mechanical stability, degradation products, etc. that can potentially affect the remodelling process [4].…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyapatite (HAP) is the main inorganic calcium phosphate mineral component of bone and teeth, with a general formula of Ca 10 (OH) 2 (PO 4 ) 6 . The close chemical similarity of HAP to natural bone has led to extensive research efforts to use synthetic HAP as a bone substitute and/or replacement in therapeutic cases [3,4].…”
Section: Introductionmentioning
confidence: 99%